METHOD FOR REMOVAL AND IDENTIFICATION OF CORONOVIRUSES FROM BLOOD BY MEANS OF LECTIN-AFFINE HEMODIALYSIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The coronavirus, which has now taken over the world in a short period of time, is a virus that resembles the causative agent of atypical syphilis (SARS), a family of viruses known as TORS. This causes chronic illness. We know that as a result of this disease, many people died prematurely and the economic development of the entire world has plummeted. In such conditions, the treatment of coronavirus disease by the method of lectin-affinity hemodialysis, obtained using lectin isolated from local raw materials, is an urgent problem.